2017
DOI: 10.1080/10503307.2017.1393576
|View full text |Cite
|
Sign up to set email alerts
|

Predicting dropout in adolescents receiving therapy for depression

Abstract: There may be little about depressed adolescents' presentation prior to therapy starting that indicates their risk of dropout. However, within-treatment factors indicated that warning signs of dropout may be identifiable during the initial phase of therapy. Identifying and targeting early treatment indicators of dropout may provide possibilities for improving engagement. Clinical and methodological significance of this article: In the literature, a great deal of attention has been paid to child and family facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 69 publications
4
53
0
4
Order By: Relevance
“…Similar to adult psychotherapy, the therapeutic alliance is consistently associated with positive changes in youth mental health treatment (Shirk, Karver & Brown, ). Moreover, recent research also finds that a poor therapeutic alliance predicts dropout among adolescents (de Haan et al., ; O'Keeffe et al., ), and that adolescents initially hope for a strong and collaborative therapeutic relationship at the onset of therapy (Midgley et al., ). Another study finds that adolescents who take ownership in the therapy process have less likelihood of dropout (Philips, Werbart & Schubert, ), underscoring the importance of establishing a solid and reciprocal relationship with the adolescent client.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to adult psychotherapy, the therapeutic alliance is consistently associated with positive changes in youth mental health treatment (Shirk, Karver & Brown, ). Moreover, recent research also finds that a poor therapeutic alliance predicts dropout among adolescents (de Haan et al., ; O'Keeffe et al., ), and that adolescents initially hope for a strong and collaborative therapeutic relationship at the onset of therapy (Midgley et al., ). Another study finds that adolescents who take ownership in the therapy process have less likelihood of dropout (Philips, Werbart & Schubert, ), underscoring the importance of establishing a solid and reciprocal relationship with the adolescent client.…”
Section: Discussionmentioning
confidence: 99%
“…3 37% of adolescents dropped out of their allocated therapy, and 10% did not take up the therapy on offer. 9 The hypothesis tested in this study was that one-year after the end of treatment for depression adolescents who dropped out of their offered therapy would have poorer outcomes than adolescents who completed therapy.…”
Section: Designmentioning
confidence: 99%
“…Participants were retrospectively classified as dropouts if they took up the therapy on offer but ended it without the mutual agreement of their therapist, as determined by the therapist's 'end of treatment' form, regardless of how many sessions they attended. This definition was selected as is the most well accepted in the contemporary dropout literature, 9 and allows for the reality that dropout can happen after any number of sessions. To address the limitation that this definition includes adolescents that attended a significant proportion of planned sessions and those who dropped out at an early stage, sensitivity analyses were conducted to consider different approaches to defining dropout, based on when dropout occurred.…”
Section: Operationalising Therapy Completion and Dropoutmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore around 35% or so of depressed teenagers may drop out of a priori planned treatments, without agreement with the therapist thereby serving an early warning for putative nonresponse (Warnick, Gonzalez, Weersing, Scahill, & Woolston, 2012). The IMPACT study reported that poor therapeutic alliance and missed sessions early (eg first month) may index later drop out (O'Keeffe et al, 2017).…”
Section: Treatment Nonresponsementioning
confidence: 99%